Catalyst Activation, Deactivation, and Degradation in Palladium‐Mediated Negishi Cross‐Coupling Reactions. Issue 14 (24th February 2015) - Böck, Katharina; Feil, Julia E.; Karaghiosoff, Konstantin; Koszinowski, Konrad
Abstract Pd‐mediated Negishi cross‐coupling reactions were studied by a combination of kinetic measurements, electrospray‐ionization (ESI) mass spectrometry, 31P NMR and UV/Vis spectroscopy. The kinetic measurements point to a rate‐determining oxidative addition. Surprisingly, this step seems to involve not only the Pd catalyst and the aryl halide substrate, but also the organozinc reagent. In this context, the ESI‐mass spectrometric observation of heterobimetallic Pd–Zn complexes [L2PdZnR]+ (L=S‐PHOS, R=Bu, Ph, Bn) is particularly revealing. The inferred presence of these and related neutral complexes with a direct Pd–Zn interaction in solution explains how the organozinc reagent can modulate the reactivity of the Pd catalyst. Previous theoretical calculations by González‐Pérez et al. (Organometallics 2012, 31, 2053) suggest that the complexation by the organozinc reagent lowers the activity of the Pd catalyst. Presumably, a similar effect also causes the rate decrease observed upon addition of ZnBr2. In contrast, added LiBr apparently counteracts the formation of Pd–Zn complexes and restores the high activity of the Pd catalyst. At longer reaction times, deactivation processes due to degradation of the S‐PHOS ligand and aggregation of the Pd catalyst come into play, thus further contributing to the appreciable complexity of the title reaction.